Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1017/s1138741600002377
|View full text |Cite
|
Sign up to set email alerts
|

Grandparent-Grandchild Relationships from the Children's Perspective: Shared Activities and Socialization Styles

Abstract: The objective of this study is to describe the relationships between grandchildren and their favourite grandparents, by studying the socialization styles used by latter and the shared activities undertaken. The participants were 360 children between 10 and 12 years old, who completed the grandparent-grandchild relationship questionnaire of Rico, Serra and Viguer (2001) and the socialization questionnaire of Rey and Ruiz (1990). The results demonstrate the importance of gender and family line in the selection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 23 publications
3
17
0
11
Order By: Relevance
“…In this line, the socializing practices used by current grandparents are consistent with the authoritative style, in contrast with the authoritarian style that was predominant in the past. These results agree with those found by other authors (Blackwelder & Passman ; Pratt et al ; Viguer et al ). Coinciding with these results, Grusec and Goodnow () stated that dialogue was the main predictor of values' internalization, because it allows value discussion with the socializing agents and, subsequently, individuals make their own through internal dialogue.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In this line, the socializing practices used by current grandparents are consistent with the authoritative style, in contrast with the authoritarian style that was predominant in the past. These results agree with those found by other authors (Blackwelder & Passman ; Pratt et al ; Viguer et al ). Coinciding with these results, Grusec and Goodnow () stated that dialogue was the main predictor of values' internalization, because it allows value discussion with the socializing agents and, subsequently, individuals make their own through internal dialogue.…”
Section: Discussionsupporting
confidence: 94%
“…Roberto and Stroes () found that grandparents were described by university students as important socializing agents through social value transmission, especially grandmothers, except values related to occupations and instrumental activities, where grandparents had a higher influence. Similar results have been found in more recent studies (Pratt et al ; Viguer et al ; Goodsell et al ). Also, Bengtson et al .…”
Section: Introductionsupporting
confidence: 92%
“…Penelitian terdahulu membuktikan bahwa pengalaman menjadi kakek dan nenek merupakan pengalaman yang kompleks dan beragam. Nenek dan kakek memiliki peran dukungan penting dalam hal emosional dan finansial untuk ibu dan anak (Viguer et al, 2010).…”
Section: Pendahuluanunclassified
“…Mattanah (2005) menyatakan bahwa orang tua yang terlalu mendorong atau melarang serta terlalu banyak membantu anak justru akan mengakibatkan anak merasa tidak mampu atau merasa bersalah jika tidak berhasil sehingga anak menjadi tidak mandiri (Weiss, 2006). Sementara, gaya pengasuhan yang diterapkan nenek biasanya bersifat permisif (Viguer et al, 2010). Gaya pengasuhan nenek yang demikian dikhawatirkan dapat menghambat perkembangan kemandirian dan kognitif cucu yang diasuh oleh nenek.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation